2005
DOI: 10.1097/01.mlg.0000163765.88158.86
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Response Genotype and Risk of Differentiated Thyroid Cancer: A Case-Control Analysis

Abstract: In this case-control analysis, the XRCC3 18067T polymorphism is associated with DTC risk. However, such work needs confirmation in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 29 publications
(76 reference statements)
3
45
0
Order By: Relevance
“…The product of XRCC3 is a RAD51 paralog necessary for the binding and stabilization of the latter during DNA repair. In our study, the increased risk of rs861539 polymorphism in thyroid cancer is comparable to previous results reporting significant associations with thyroid cancer risk [36-40]. Nevertheless, many studies have found no evident correlation between XRCC3 polymorphisms and thyroid cancer [41, 42].…”
Section: Discussionsupporting
confidence: 88%
“…The product of XRCC3 is a RAD51 paralog necessary for the binding and stabilization of the latter during DNA repair. In our study, the increased risk of rs861539 polymorphism in thyroid cancer is comparable to previous results reporting significant associations with thyroid cancer risk [36-40]. Nevertheless, many studies have found no evident correlation between XRCC3 polymorphisms and thyroid cancer [41, 42].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, assessment of allele frequency distribution revealed a fairly significant involvement of XRCC3 T241M variant allele (T) on individual susceptibility toward DTC (p value: 0.058). The results are similar to earlier reports with regard to differentiated thyroid cancer in Caucasian Portuguese (Bastos et al, 2009) and a non-Hispanic white population (Sturgis et al, 2005). They found XRCC3 variant allele was associated with a twofold increased risk of thyroid cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Data on the TP53 and XRCC3 polymorphisms associations are quite limited (Hillebrandt et al 1997, Boltze et al 2002, Granja et al 2004, Sturgis et al 2005, Rogounovitch et al 2006. Therefore, in this study, we addressed the relation of SNPs in aforementioned DNA damage response genes to the risk of PTCs of different etiology.…”
Section: Introductionmentioning
confidence: 96%
“…The XRCC3 Thr241Met polymorphism has been controversially associated with different human malignancies (Han et al 2006). Sturgis et al (2005) reported 241Met allele association with the risk of differentiated thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%